MASLAHAT MEMELIHARA HARTA DALAM SISTEM EKONOMI ISLAM - Iswandi, Andi (SALAM: Jurnal Sosial dan Budaya Syar-i, 2014)
Abstract: The Benefits of Maintaining Property in Islamic Economic System. property in the Islamic economic system has an important position. Related in business activities of economic and ritual worship, in  Sharia maqoshid, preserve or maintain the property is one of important point. It is the intent and purpose of God in order to give the benefit of the people to pray to serve as guidelines in the business and dealing with. The benefit in preserving and maintaining the property is an economic system that has been set by Allah swt. Economic system does not belong by any religion other than Islam. This system provides guidance on how humans earn their living, consuming materials, conduct transactions, distribute assets, and conduct religious activities like charity, donation and alms. Keywords: Benefits, Maintaining Property, Sharia Maqoshid, Islamic Economic System Abstrak: Maslahat Memelihara Harta Dalam Sistem Ekonomi Islam. Harta di dalam sistem ekonomi Islam memiliki kedudukan yang penting. Dalam kaitannya dengan kegiatan bisnis ekonomi dan ritual ibadah, harta diperhatikan betul, sehingga di dalam maqoshid syariah menjadikannya salah satu point penting yaitu, memelihara atau menjaga harta. Hal ini adalah maksud dan tujuan Tuhan dalam rangka memberikan kemaslahatan kepada manusia untuk kiranya dijadikan sebagai pedoman di dalam berbisnis dan bermuamalah. Kemaslahatan di dalam memelihara ataupun menjaga harta merupakan sistem ekonomi yang diberikan Allah Swt., yaitu sistem ekonomi yang tidak dimiliki oleh agama lain selain agama Islam. Sistem inilah yang memberikan pedoman bagaimana manusia mencari nafkah, mengkonsumsi materi, melakukan transaksi jual-beli, mendistribusikan harta, dan melakukan kegiatan ibadah seperti zakat, infak dan sedekah. Kata Kunci: maslahat, memelihara harta, maqoshid syariah, sistem ekonomi IslamDOI:10.15408/sjsbs.v1i1.1522